Investigation of the Effects of Mitochondrial-Derived Peptide (MOTS-c) on the Control of Feeding in Obese Rats - Durmus, Merve; Tekin, Suat; Onalan, Ebru Etem; Sandal, Suleyman (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY